Long-term outcome after surgical correction of sinus venosus defect in a nationwide register-based cohort study - Muroke Valtteri; Jalanko Mikko; Haukka Jari; Anttila Vesa; Pätilä Tommi; Sinisalo Juha (Elsevier Ireland Ltd, 2025)
Objectives: Long-term results after sinus venosus defect (SVD) closure are sparse and many studies lack a proper control cohort. This nationwide cohort evaluated the long-term outcome after SVD surgery.
Methods: The study enrolled every surgical SVD correction from the nationwide hospital discharge registry (FHDR) and surgical registries of two tertiary centers. Patients with more complex congenital heart defects were excluded. Surgeries were performed from 1969 to 2019. Five sex and birth-year-matched controls per SVD patient were gathered from the general population.
Results: In total, 182 surgical SVD corrections were performed during the study period. The median age at the time of surgery was 8.3 years (range 0.06-75.7), and the majority (77.5%, n = 141) were under 18 years old. The median follow-up period was 18 years (range 0.1-53). There was no significant difference in mortality during the follow-up (logrank p = 0.62, MRR 0.78, 95% CI: 0.30-2.0). However, SVD patients had elevated risk for new-onset atrial fibrillation (RR 4.9, 95% CI: 2.2-10.9), heart failure (RR 4.0, 95% CI: 1.2-13.2), ischemic heart disease (4.3, 95% CI, 1.5-11.7), migraine (RR 3.6, 95% CI: 1.5-9.1) and sick sinus syndrome, II- or III-degree AV-block or pacemaker implantation (RR 11.3, 95% CI: 2.9-43.8).
Conclusion: Young patients with SVD have an excellent survival prognosis after the surgery. Risk for sick sinus syndrome or conduction disorders, atrial fibrillation, and heart failure remains elevated in the long-term follow-up.
Keywords: Atrial fibrillation; Atrial septal defect; Congenital heart disease; Heart failure; Mortality; Sinus venosus defect.